MAPPING POTENTIAL BASED ON CHARACTERISTICS OF TOURISM OBJECTS IN TUAMESE VILLAGE - Mariano Sengkoen; Melkianus Suni; Ignasius Usboko (International Review of Practical Innovation, Technology and Green Energy (IRPITAGE), 2024)
Tuamese Village, Biboki Anleu District, North Central Timor Regency is a tourist village, as stated in the Decree of the Regent of North Central Timor Number 405/KEP/HK/V/TTU/2020 concerning Tourist Villages..Based on the 2022 research report of the author team to the University of Timor, Tuamese Village has potential tourist attractions that have not been properly inventoried and mapped. This causes the community to have a lack of understanding of the natural wealth, culture, and activities as tourism potential; hinders the village government in formulating development policies and promotional content for tourism potential in a holistic and integrated manner; and reduces public interest in visiting or investing in Tuamese Village. Therefore, the team conducted an inventory and mapping of potential tourist attractions in order to support its existence as a tourist village. The team conducted a complete participatory exploration and mapping using the ArcGis 10 application. The direct output of community service is an inventory document and map of potential tourist attractions in Tuamese Village. The inventory and map of potential tourist attractions contain Cultural Tourism, Recuperational Tourism, Commercial Tourism, Sport Tourism, Social Tourism, Religious Tourism, and Marine Tourism. In addition, the potential for tourism objects in Tuamese Village is carried out because of the unique natural construction attractions in a particular place, such as hills, plantations, oceans, beaches, and others. The main factor inhibiting community participation in the management of the Bukit Tuamese tourist attraction is the absence of formal legal regulations at the village level, such as Village Regulations, which guarantee inclusive community participation.